Strategy for Quality Assurance of Leading School Education in Lamongan Regency - Mumayyizah Mumayyizah; Sujarwanto Sujarwanto; Nunuk Hariyati; Hanandita Veda Saphira (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This study aimed to explore and analyse the implementation of quality assurance at Junior High School Muhammadiyah 12 Sendangagung Paciran, Lamongan Regency. The main focus is on the planning, implementation, control, and development of the internal quality assurance system, and the role and involvement of the principal, teachers, and school committee in the process. Method: This study used a qualitative method with a case study type. The participants in this study were principals, teachers, and school committees. Data were collected through in-depth interviews with the selected participants. Data analysis was conducted using a thematic approach, which involved interview transcription, data coding, theme identification, and interpretation of results. Results: The results of the study indicated that Junior High School Muhammadiyah 12 Sendangagung Paciran implemented quality assurance through mature strategic planning, structured program implementation, strict quality control, and continuous development. The principal plays a central role as a leader who directs quality assurance policies and strategies. Teachers act as the main implementers in the learning process, and the school committee provides support and evaluation for the programs being run. The challenges faced include limited resources and the need to build teacher capacity. Novelty: This study provides a new contributes to the understanding of quality assurance in leading schools, especially in the context of junior high schools in Indonesia. This study highlights the importance of collaboration between various parties in quality assurance and shows how a quality assurance approach can be implemented effectively in a local context. These findings are expected to serve as a reference for other schools that want to improve the quality of their education through comprehensive quality assurance.